2019
DOI: 10.1177/2043610619846351
|View full text |Cite
|
Sign up to set email alerts
|

‘The whole world’s watching really’: Parental and educator perspectives on managing children’s digital lives

Abstract: Teachers are under increased pressure to teach children digital skills, and parents are having to manage children’s online presence as well as their offline lives. Much of the discussion surrounding the issue of children’s digital footprints highlights the potential present and future risks that children could be exposed to. While parents and teachers are expected to educate and protect children online, little is known about what parents and educators know in the Australian context and how they feel about bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…The majority were semi-structured and/or repeat interviews and focus groups, with only one study including participatory or ‘mobile methods’ in which participants showed researchers where they used digital technologies (Nansen et al, 2012). In addition, some papers reported on the same studies – that is, Buchanan et al (2019); Buchanan et al (2017) and Smahel and Wright (2014); Mascheroni et al (2014); Haddon and Livingstone (2017). However, these were included as each paper discussed different topics and/or from different perspectives.…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority were semi-structured and/or repeat interviews and focus groups, with only one study including participatory or ‘mobile methods’ in which participants showed researchers where they used digital technologies (Nansen et al, 2012). In addition, some papers reported on the same studies – that is, Buchanan et al (2019); Buchanan et al (2017) and Smahel and Wright (2014); Mascheroni et al (2014); Haddon and Livingstone (2017). However, these were included as each paper discussed different topics and/or from different perspectives.…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…Frequently appearing in this theme was the emotionality of the ‘conduct’ risk of cyberbullying. This was explored in several papers (Baas et al, 2013; Buchanan et al, 2019; McInroy and Mishna, 2017) and from different stakeholder perspectives (children, parents and educators). As emphasised by the mother of a pre-teen in the quotation below:They’re basically – that sort of thing is bringing home the schoolyard bullying into the house and it’s no longer a schoolyard, it’s now more – like every day, constantly, which is worse than the schoolyard .…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…It is important to note that in most countries there are currently no policies securing children’s right to online privacy, and the decision on whether and how to disclose information online is left to the parents or guardians (Lavorgna et al, 2022). This makes them the ‘digital custodians’ (Buchanan et al, 2019: 175) of the personal information of their children online, but they are often unprepared to the role (Brosch, 2018; Steinberg, 2017).…”
Section: Protecting Digitised Identity Information: Prospects Impedim...mentioning
confidence: 99%
“…A core problem is that much of the focus of studies exploring digital parenting has been on offering guidance to adults on how to best manage screens and media for their children (Uhls, 2015). But parents (and, more generally, guardians, including teachers), whilst being expected to educate and protect children online, are unprepared for their role as ‘digital custodians’ (Buchanan et al, 2019: 175). They should be the first line of defence, but at times are not (Brosch, 2018).…”
Section: Introductionmentioning
confidence: 99%